HAMBATAN NOTARIS DALAM PEMBUATAN AKTA BADAN HUKUM PERKUMPULAN - RINA RINA (PREMISE LAW JURNAL, 2016)
Drawing up a deed of a legal entity association involves a Notary as a public officer who is empowered to draw up deeds.The problems of the research were how about the position of an association established as a legal entity and how about a Notary’s responsibility for the deed of legal entity association after the issuance of the Regulation of the Minister of Law and Human Rights No. 6/2014 on the Validation of Legal Entity Association. The research used judicial normative and qualitative method, based on legal provisions and respondents’ opinions. Usually, notary usually used the modeling of foundation deed in drawing up legal entity association deeds which contained the statutes of association since there was the resemblance between foundation and legal entity association and its registration was done manually. However, since the issuance of the Regulation of the Minister of Law and Human Rights No. 6/2014 on the Validation of Legal Entity Association, a Notary has to comply with this regulation in drawing up legal entity association deeds, including the registration of legal entities which is done electronically (online system). The problem is that the statutes of the association is not clearly organized so that a Notary as a State official who has the authority to draw up authentic deeds encounters obstacles in drawing up legal entity association deeds. Keywords: Legal Entity Association, Notarial Deed, Regulation of the Minister of Law and Human Rights No. 6/2014 on the Validation of Legal Entity Association